Congenital myasthenic syndromes and the formation of the neuromuscular junction. - Beeson, D; Webster, R; Cossins, J; Lashley, D; Spearman, H; Maxwell, S; Slater, C; Newsom-Davis, J; Palace, J; Vincent, A (2008)
The congenital myasthenic syndromes (CMS) are a heterogeneous group of disorders affecting neuromuscular transmission. Underlying mutations have been identified in at least 11 different genes. The majority of CMS patients have disorders due to mutations in postsynaptic proteins. Initial studies focused on dysfunction of the acetylcholine receptor (AChR) itself as the major cause of CMS. However, it is becoming apparent that mutations of proteins involved in clustering the AChR and maintaining neuromuscular junction structure form important subgroups. Analysis of the mutations in the AChR-clustering protein, rapsyn, show diverse causes for defective AChR localization and suggest that the common mutation rapsyn-N88K results in AChR clusters that are less stable than those generated by wild-type rapsyn. More recently, mutations in the newly identified endplate protein Dok-7 have been shown to affect AChR clustering and the generation and maintenance of specialized structures at the endplate. Dok-7 binds MuSK and many of the mutations of DOK7 impair the MuSK signaling pathway. Components of this pathway will provide attractive gene candidates for additional forms of CMS. The phenotypic characteristics of the different CMS in which muscle groups may be differentially affected not only provide clues for targeted genetic screening, but also pose further intriguing questions about underlying molecular mechanisms.